2017
DOI: 10.1007/s12182-017-0156-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oil recovery by nonionic surfactants considering micellization, surface, and foaming properties

Abstract: Surfactants for enhanced oil recovery are important to study due to their special characteristics like foam generation, lowering interfacial tension between oleic and aqueous phases, and wettability alteration of reservoir rock surfaces. Foam is a good mobility control agent in enhanced oil recovery for improving the mobility ratio. In the present work, the foaming behavior of three nonionic ethoxylated surfactants, namely Tergitol 15-S-7, Tergitol 15-S-9, and Tergitol 15-S-12, was studied experimentally. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 61 publications
(60 reference statements)
1
17
0
2
Order By: Relevance
“…Foams are thermodynamically unstable due to their high interfacial free energy. The stability of the foam is mainly controlled by the drain speed and intensity of the interfacial film (Bera et al, ; Xu et al, ). The foam stabilities are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Foams are thermodynamically unstable due to their high interfacial free energy. The stability of the foam is mainly controlled by the drain speed and intensity of the interfacial film (Bera et al, ; Xu et al, ). The foam stabilities are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CMC is an important aspect to study where at a concentration above the CMC’s value, the adsorption of the surfactant at the interface becomes insignificant. This indicates that the optimum reduction of surface or interfacial tension has been achieved [11] , [15] . Therefore, the selected surfactant concentration should be always above the CMC to ensure that formation of micelles, demonstrating an adequate concentration has been attained to obtain maximum efficiency in reducing IFT [16] .…”
Section: Introductionmentioning
confidence: 82%
“…However, there are some limitations to surfactant flooding techniques, such as the high cost of surfactants, surfactant loss during operation due to adsorption by reservoir rocks, and their toxicity to the environment, leading to high production costs and toxicity, especially in a sea environment (Bera et al, 2017). Thus, many studies have suggested that surfactants synthesized from natural resources could avoid the negative environmental impacts from surfactant loss during surfactant flooding, and still provide high recovery rate (Arabloo et al, 2015;Barati-Harooni et al, 2016;Iglauer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%